Perancangan dan Pembuatan Website Ujian Online Jurusan Kimia Analisis - Arny Marunduri (Universitas Putra Indonesia YPTK Padang, 2020)
Author designing websites online exam easily used when conducting examinations at SMAK SMK Padang. This study aims to determine the validity, practicalities and Effectiveness Website Designing and Making Class X Examination Department of Chemical Analysis In SMAK SMK Padang Academic Year 2018/2019. This study uses research and development (R & D) 4D. Sabjek study amounted to 31 people, with design and development steps are as follows. (1) Define, in step define will do a needs analysis of the system that we created (2) Design, at this step is to design tehadap system will be made (3) Develop, in this step will be the stage of assessment of the system created and ( 4) Disseminate, at this stage of deployment of products that have been created. The validity of the test results by the experts overall assessment of the validator test Website Online Class X Exam Chemical Analysis Department at SMK Padang SMAK by 89.87%, so the rate can be interpreted validity Invalid use. Results of votes overall assessment practicalities test the practicalities of the Website Online Class X Exam Chemical Analysis Department at SMK Padang SMAK by 90.84%, so the rate can be interpreted praktikalitasnya Very Practical use. Results of votes overall effectiveness test assessing the effectiveness of the Website Online Class X Exam Chemical Analysis Department at SMK Padang SMAK by 89.44%, so that their effectiveness can be interpreted Very Good used. In conclusion, based on the assessment along with expert input as well as the results of the field trial Website Online Exam as the system is tested the feasibility, advantages, and can be used onnew admissions process SMAK SMK Padang.